Structure-Conduct-Performance of Cotton Market: The Case of Metema District, Ethiopia - Bosena, T.; Bekabil, F.; Gebremedhin, Berhanu; Hoekstra, Dirk (2011)
The efficiency of cotton market chain that can have great influence on farm level supply of marketable cotton was evaluated for Metema District of Ethiopia, using structure-conduct-performance approach. Market concentration ratio (CR4) at District level was 49.76 percent and there were observed barriers to entry into the cotton market. These structural characteristics indicate oligopolistic structure of cotton market at the District level. Cotton market at ginneries and textile factories were highly oligopolized by two ginneries and three textile factories. Buying, selling, and pricing strategies, which are indicators of market conduct showed deviation of cotton market from competitive market norms. The performance of cotton market chain analyzed using Marketing Margins supplemented with analysis of costs incurred and gross profits generated for different market chain actors, showed poor performance of the chain. In the chain farmers are the most disadvantaged chain actors